NOTICING GRAMMATICAL PATTERN ON ONLINE SHORT STORIES BY LEARNING GRAMMAR THROUGH GRAMMAR TRANSLATION METHOD - Edy Suseno (Sanata Dharma University Yogyakarta, 2021)
Memorizing structure pattern is very tiring and often resulting in failure. Learners often try to adapt it in conversation and writing, but it sometimes ends up with unsatisfactory. The process of implementing grammar-translation methods to explain how to structure patterns built and used leads learners to understand it clearly and it could decrease the level of confusion significantly. Furthermore, to make the patterns learners learned to stay some longer in their minds, they can notice the grammar content in short stories. The use of online short stories could ease them to read more to support noticing. Thus, learning grammar pattern boosted by the grammar-translation method and using online short stories to notice grammatical pattern could develop students’ proficiency in implementing grammar both in spoken and written.